Perhitungan Struktur Aman terhadap Gempa Gedung Hotel Nunusaku di wilayah Kota Ambon - Yulius Sovian Pesung; Vector R. R Hutubessy; Herry Henry Roberth (Universitas Pahlawan Tuanku Tambusai, 2025)
The writing of this final project aims to obtain the strength of the building structure that is safe against earthquakes, with a large magnitude force. Based on the title